Solar Cycle Variations and its Effects on El Niño/La Niña Behaviour - Iratius Radiman; Dhani Herdiwidjaja; Zadrach L. Dupe; Chatief Kunjaya; Muhammad Irfan Hakim (Jurnal Matematika & Sains, 2003)
Variations in the Solar Cycle has been known for a long time. The Solar Cycle is observed to vary from 14 to 8 years in length. The reconstructions of the annual solar total irradiance since the beginning of Maunder Minimum (from year 1600) to year 2000 show that there are envelopes of groups sunspot numbers. The intensities delineated by the envelopes are consistent with the range of CaII brightness. The timelength of the envelopes corresponds to long term variabilities such as the Gleissberg Cycle of 88 and 124 years period. A close correlation between total irradiance and sunspot number from 1610 to 2000 is found to be 0.88. Although the work of Labitzke and van Loon has clearly shown the existence of an oscillation in many atmospheric parameters with a period in the vicinity of 11 years and a phase that is related to that of solar activity, there is reluctance to accept a relationship to the 11-year solar cycle. Therefore this study aimed to pursue the investigations further by determining the correlation coefficients to lower trophospheric layers. Our studies reveal to results, which we summarized as follows: A weak correlation at 27 month delay is found between solar activities and the El Niño/La Niña phenomena. The next El Niño/La Niña event is expected to occur from year 2002 until mid 2003. A major change in the pattern of the solar cycle since 1700 appears. The sun is seen to be more frequent in its active states over the last 100 years. The length of the cycle is becoming shorter. The solar cycles modulate from 5, 8, 12 and 25-year period obtained from its total irradiance plot. The 5-year period coincides very well within the El Niño/La Niña period of 2 to 7-year. The El Niño/La Niña phenomenon has a 10-12 month duration. Every El Niño/La Niña event is separated from 24 to 84 months duration in an irregular pattern. Every El Niño/La Niña event is unique. These conclusions are drawn after decomposing the SST Anomaly Index through applied Fourier Transform. The effect of the solar cycle variations is to generate long period harmonics in the coming El Niño/La Niña events. We expect that more variability in climate will occur in the coming decade.